2019
DOI: 10.1038/s41467-018-08255-x
|View full text |Cite
|
Sign up to set email alerts
|

BAP1 complex promotes transcription by opposing PRC1-mediated H2A ubiquitylation

Abstract: In Drosophila, a complex consisting of Calypso and ASX catalyzes H2A deubiquitination and has been reported to act as part of the Polycomb machinery in transcriptional silencing. The mammalian homologs of these proteins (BAP1 and ASXL1/2/3, respectively), are frequently mutated in various cancer types, yet their precise functions remain unclear. Using an integrative approach based on isogenic cell lines generated with CRISPR/Cas9, we uncover an unanticipated role for BAP1 in gene activation. This function requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
113
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 62 publications
14
113
0
2
Order By: Relevance
“…This is specifically associated with the inactivation of the H2AK119ub1 specific de-ubiquitinase BAP1 that occurs with high frequency in uveal melanoma ($45%) and mesothelioma ($22%) as well as in several other tumor types with lower frequencies like atypical Spitz tumors ($11%), clear cell renal cell carcinoma ($18%), ovary ($5%), and colon-rectum ($3%) (Carbone et al, 2013). BAP1 inactivation always resulted in strong accumulation of H2AK119ub1 levels (Campagne et al, 2019) and, based on the canonical model by which PRC2 controls upstream PRC1 activity, it was proposed that BAP1-deficient tumors could benefit from PRC2 inhibition (LaFave et al, 2015). Our data argue against this possibility, placing H2AK119ub1 deposition in a central position to control PcG-mediated repression upstream to PRC2 and cPRC1 activities.…”
Section: Discussionmentioning
confidence: 99%
“…This is specifically associated with the inactivation of the H2AK119ub1 specific de-ubiquitinase BAP1 that occurs with high frequency in uveal melanoma ($45%) and mesothelioma ($22%) as well as in several other tumor types with lower frequencies like atypical Spitz tumors ($11%), clear cell renal cell carcinoma ($18%), ovary ($5%), and colon-rectum ($3%) (Carbone et al, 2013). BAP1 inactivation always resulted in strong accumulation of H2AK119ub1 levels (Campagne et al, 2019) and, based on the canonical model by which PRC2 controls upstream PRC1 activity, it was proposed that BAP1-deficient tumors could benefit from PRC2 inhibition (LaFave et al, 2015). Our data argue against this possibility, placing H2AK119ub1 deposition in a central position to control PcG-mediated repression upstream to PRC2 and cPRC1 activities.…”
Section: Discussionmentioning
confidence: 99%
“…This is specifically associated with the inactivation of the H2AK119ub1 specific de-ubiquitinase BAP1 that occurs with high frequency in Uveal Melanoma (~45%) and Mesothelioma (~22%) as well as in several other tumour types with lower frequencies like Atypical Spitz tumours (~11%), Clear Cell Renal Cell Carcinoma (~18%), Ovary (~5%), and Colon-rectum (~3%) (Carbone et al, 2013). BAP1 inactivation always resulted in strong accumulation of H2AK119ub1 levels (Campagne et al, 2019) and, based on the canonical model by which PRC2 controls upstream PRC1 activity, it was proposed that BAP1 deficient tumours could benefit from PRC2 inhibition (LaFave et al, 2015). Our data argues against this possibility placing H2AK119ub1 deposition in a central position to control PcG-mediated repression upstream to PRC2 and cPRC1 activities ( Figure 7C model).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the simplest model proposes that SWI/SNF mutations drive transformation through gain of PRC2 function and silencing of tumour suppressor genes, non-catalytic activity of EZH2 has also been implicated and it has been suggested that combined loss of both SWI/SNF and PRC2 function could induce cell death due to global transcriptional dysregulation rather than derepression of specific PRC2 targets 134,140,142,145 . BAP1 is a deubiquitinase targeting histone H2AK119 that opposes polycomb mediated silencing 146 , however, sensitisation to EZH2 inhibitors following BAP1 loss appears to be cell type specific and has been observed in mesothelioma but not uveal melanoma 139,147 . PRC2 can also function as a tumour suppressor and recurrent inactivating mutations in EZH2 have been reported in myelodysplastic syndrome and chronic myeloproliferative neoplasms [148][149][150][151][152] .…”
Section: Deconvoluting the Contribution Of Each Enzyme Affected By D2mentioning
confidence: 99%